2013
DOI: 10.1186/1471-2229-13-156
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterisation of three members of the Vitis viniferaL. carotenoid cleavage dioxygenase gene family

Abstract: BackgroundIn plants, carotenoids serve as the precursors to C13-norisoprenoids, a group of apocarotenoid compounds with diverse biological functions. Enzymatic cleavage of carotenoids catalysed by members of the carotenoid cleavage dioxygenase (CCD) family has been shown to produce a number of industrially important volatile flavour and aroma apocarotenoids including β-ionone, geranylacetone, pseudoionone, α-ionone and 3-hydroxy-β-ionone in a range of plant species. Apocarotenoids contribute to the floral and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
135
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(146 citation statements)
references
References 63 publications
10
135
0
Order By: Relevance
“…As shown in Fig. 5, the degree of conservation was poor in these proteins, which supports the view reported previously for other plants (Auldridge et al 2006a, b;Lashbrooke et al 2013;Vallabhaneni et al 2010;Walter et al 2010).…”
Section: Multiple Sequence Alignments and Phylogenetic Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…As shown in Fig. 5, the degree of conservation was poor in these proteins, which supports the view reported previously for other plants (Auldridge et al 2006a, b;Lashbrooke et al 2013;Vallabhaneni et al 2010;Walter et al 2010).…”
Section: Multiple Sequence Alignments and Phylogenetic Analysissupporting
confidence: 90%
“…It suggested that a duplication event had occurred in the course of evolution. The members of the CCD4 enzymes, as well as those from other plants, often include two copies, namely CCD4a and CCD4b (Huang et al 2009;Lashbrooke et al 2013;Ohmiya et al 2006;Rubio et al 2008;Vallabhaneni et al 2010). The copies of CCD8 are variable in different plant species.…”
Section: Resultsmentioning
confidence: 99%
“…However, the transcripts from two grapevine CCD4 genes were recently found to be similarly ripening induced (Lashbrooke et al, 2013). As stated above and despite similar substrate and product preferences of CCD1 and CCD4 in vitro (Vogel et al, 2008;Bruno et al, 2015), results from ccd4-1 and ccd1-1 ccd4-1 mutants are in favor of CCD4 being responsible for AG formation in planta.…”
Section: Ccd4 Is Mainly Responsible For Ag Formationmentioning
confidence: 78%
“…In grapevines, this technology has been recently applied to analyze the function of several genes such as VviAdh [75], VviPIP2 [76], VviCCD1 [77], and VviWRKY33 [78]. Likewise, this method has been proved to be very useful for transgenic complementation [79][80][81], technical studies [82][83][84][85][86][87], promoter analysis [88][89][90][91], subcellular localization analysis [92], and protein production [69,93] in grapevine.…”
Section: Indirect Gene Transfer Methods: Agrobacterium-mediated Transmentioning
confidence: 99%
“…For instance, the compatibility of A. tumefaciens strains with the plant species represents an important variable to be considered in this kind of assay. Thus, the strains most efficiently used for gene transfer into grapevine are probably C58C1 (pCH32) [69,78,86] and EHA105 [75,77,82,83,85,88,90], which contain extra copies of vir genes that make them hypervirulent [61].…”
Section: Indirect Gene Transfer Methods: Agrobacterium-mediated Transmentioning
confidence: 99%